Human resource management in the sport and leisure industry - Wolsey, Chris. 352360; Abrams, Jeff, 1956- 201950; Minten, Sue. (Milton Park, Abingdon, Oxon ; New York : Routledge, 2011)
"HRM in the Leisure and Sport Industry provides a comprehensive course textbook and reference for students of HRM, business, sports and leisure management. By its very nature service, leisure and sport are staff intensive sectors, making effective human resource management and development central to understanding the business, and to business success. Containing wide ranging industry specific case studies and full explanation of all key HR issues, this text provides a unique resource to help students develop their understanding of strategic HR theory and practice. HRM in the Leisure and Sport Industry is a dependable and comprehensive resource for students and professionals in the sport and leisure business"--